IMPLEMENTATION OF PARKING SERVICE RETRIBUTION POLICY ON THE EDGE OF PUBLIC ROADS OF SUKABUMI CITY - Delia Arsa Aulia Putri; M Rijal Amirulloh; Andi Mulyadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The title of this study is